A gem of a girl ( in one volume) - Shivam; All India Confederation of the Blind (New Delhi : Children Book's Trust)
Anjana has the looks and the gem Muthu has his eye on both If not the girl, the gem he must have What stops him?
Keywords: Literature; English literature; Indian literature